Performance of passive design strategies in hot and humid regions. Case study: Tangerang, Indonesia. Issue 4 (4th July 2021) - Chen, Yanmeng; Mae, Masayuki; Taniguchi, Keiichiro; Kojima, Teruki; Mori, Hiroshi; Trihamdani, Andhang Rakhmat; Morita, Kohei; Sasajima, Yukie
ABSTRACT: The building sector is one of the largest energy consumers worldwide. Especially in the hot-humid Southeast Asian region, this sector consumes about 30% of primary energy demand. This is mainly dominated by air conditioning systems to provide space cooling and dehumidifying. In this paper, three passive design strategies to reduce cooling energy and attain a good daylight environment in an office in Tangerang, Indonesia, will be evaluated using both measurement and simulation methods. Improving thermal insulation, natural ventilation, and solar shading are the strategies studied in this paper. The measurement result shows that the excessive daylight can be reduced by solar shading and the indoor temperature can be reduced by both solar shading and natural ventilation. The result of the simulation also validates the effects of shading and natural ventilation on lowering the indoor temperature and reducing the cooling load. Besides, it is proved that the difference in the building's airtightness can cause an obvious difference in the effect of natural ventilation. There will be a large potential to adopt passive design even in hot and humid regions if the strategies are applied appropriately and good performance of the building, including high airtightness and proper thermal insulation, is guaranteed.